Measuring economic order in the knowledge economy: A cross-country analysis - Jesus Matos-Vila; Joan Torrent Sellens (Internet Interdisciplinary Institute, Open University of Catalonia, 2015)
The advent of the knowledge economy has transformed the behavior of economic agents and the nature of transactions. In particular, the increase of knowledge based transactions not associated with monetary flows is weakening the significance of traditional measures of economic dynamics like gross domestic product (GDP) or national income (NI). The objective of the working paper is to improve the measurement of new economic dynamics introducing a model that measures and explains Economic Order in the knowledge economy driven by the agents of Governance, Wealth, Conflict and Mutuality. Income, a component of the Wealth agent, is an independent variable of the model. Its maximization is not an objective within the analyzed economic framework. Therefore, income and production growth are not primary goals, but instead they make a complementary contribution to Order. Besides, Welfare is not built exclusively on the optimal distribution of income, and sourced on individual utility and preferences, but on the economic order of the system. The Transaction is the vehicle that constitutes the minimal unit facilitating or preventing exchange within and among the economic agents. An empirical analysis is performed over a cross-sectional sample of quantitative and qualitative data of 142 countries of the world economy in the period 2010-2011. A Logit regression is constructed where the dependent variable explaining Order is an index denominated Disentropy. Lower income inequality (Gini) does not mean a higher level of Order. As an economy achieves more economic order Wealth becomes a less relevant agent. Human development (HDI) is positively correlated with economic order. The Disentropy linear function is normalized to obtain a Cobb-Douglas analogous function. This function is twice differentiable and its hessian is lower than zero evidencing a concave behavior of the Disentropy variable. Hence Order presents decreasing outputs to scale across the considered sample of countries. A ranking of world top ordered economies is listed probably having the following common features among them: knowledge intensive, international focus, small population, homogeneous culture, self-identity, solid institutions and mainly democratic.
Keywords: C21; O33; 330; Knowledge economy; Economic order; Disentropy; Transactionality